2018
DOI: 10.1055/s-0044-101754
|View full text |Cite
|
Sign up to set email alerts
|

Face and construct validity of a novel mechanical ERCP simulator

Abstract: Background and study aims  Simulation-based training has become an important pillar in competence-based medicine. However, limited data are available on use of simulators in training for endoscopic retrograde cholangiopancreatography (ERCP). We aimed to determine the face and construct validity of the Boškoski-Costamagna mechanical ERCP Trainer, and to assess its didactic value, as judged by experts. Methods  Participants were divided into four groups based on ERCP lifetime experience: novices, intermediate, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
(43 reference statements)
0
20
0
2
Order By: Relevance
“…23 Validation studies of these simulators revealed that operators with more clinical ERCP experience performed better on the simulators compared to those with less experience. [20][21][22][23][24] Considering previous models, our simulator contains multiple papillae that vary based on several factors, including: (1) angles or axes of the papilla, (2) common channel length, (3) angle between biliary and pancreatic ducts, and (4) location within the duodenum. Additionally, a papilla to simulate Billroth II and RYGB anatomy was included for assessment of advanced cannulation skill.…”
Section: Discussionmentioning
confidence: 99%
“…23 Validation studies of these simulators revealed that operators with more clinical ERCP experience performed better on the simulators compared to those with less experience. [20][21][22][23][24] Considering previous models, our simulator contains multiple papillae that vary based on several factors, including: (1) angles or axes of the papilla, (2) common channel length, (3) angle between biliary and pancreatic ducts, and (4) location within the duodenum. Additionally, a papilla to simulate Billroth II and RYGB anatomy was included for assessment of advanced cannulation skill.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic papilla is a newly developed insertable component in the previously described mechanical ERCP simulator, the Boškoski-Costamagna ERCP Trainer (Cook Medical, Limerick, Ireland) 2 . It can be used to perform sphincterotomy.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that ERCP seems to be an ideal platform for simulation-based training, limited data are available on simulators in training ERCP. Recently, our study group has validated a novel mechanical ERCP simulator, the Boškoski-Costamagna ERCP Trainer 2 . This simulator allows novice trainees to practice cannulation, stent placement in both common bile duct (CBD) and pancreatic duct (PD), and CBD stone extraction.…”
Section: Introductionmentioning
confidence: 99%
“…2). It has recently been validated for cannulation as well as for sphincterotomy by the Rotterdam group in two different studies [10,11].…”
mentioning
confidence: 99%